An Efficient Multi Parent Hierarchical Routing Protocol for WSNâ€™s - MADAGOUDA, BASAVARAJ K (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Wireless sensor networks (WSNs) nodes are commonly designed to work with limited resources of memory, energy and processing. The routing protocol is one of the key components of WSNs and its features impact network performance significantly. We present an efficient Multi-Parent Hierarchical (MPH) routing protocol for wireless sensor networks; its main goal is to achieve reliable delivery of data in a single sink scenario while keeping low overhead, reduced latency and low energy consumption. The main features of MPH are self-configuration, hierarchical topology, persistence according to link quality, and source routing from sink to nodes. Network performance simulations of the MPH routing protocol are carried out and compared with popular protocol, AODV. Results show that for the single sink scenario, the MPH protocol has an energy saving of 35% against AODV. MPH has 27% less overhead compared with AODV. And MPH presents a 10% increase in packet delivery compared with AODV. Finally, we present a real WSN built based on the MPH protocol, which works satisfactorily, providing an experimental demonstration of the capabilities of the protocol.Â 